RADEC Learning Model (Read-Answer-Discuss-Explain And Create): The Importance of Building Critical Thinking Skills In Indonesian Context - Pratama, Yoga Adi; Sopandi, Wahyu; Hidayah, Yayuk (International Journal for Educational and Vocational Studies, 2019)
The purpose of writing this article was  to describe RADEC learning model in building critical thinking skills. This study was  conducted because of the need for a learning model that fits the Indonesian context to build critical thinking skills that can be used at  elementary school level. This study used the literature review. This study produced  one solution to be able to build critical thinking skills using  RADEC learning model (read-answer-discuss-explain and create). The approach in learning  done by the teacher plays a role in improving critical thinking skills. The teacher needs to use a learning model that can stimulate students' critical thinking skills.